2008
DOI: 10.1016/j.ejcts.2008.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Is post-sternotomy percutaneous dilatational tracheostomy a predictor for sternal wound infections?

Abstract: Tracheostomy, often performed in high-risk patients, may further complicate recovery with sternal wound infections, including mediastinitis, therefore, patients and timing should be carefully selected for post-sternotomy tracheostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
0
12
2
1
Order By: Relevance
“…Staphylococcus aureus was the prevalent microorganism, this result was corroborated by other studies (8,25) . Regarding the mortality rate among patients with SSI, this research was 38.9%, diverging from other studies in which the frequency ranged between 2.6% and 32.1% (14,17,(22)(23)(24) . Therefore, this result indicated that the diagnosis of SSI was constituted in an aggravation of the clinical condition of the patient, which may have favored the occurrence of complications with death.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Staphylococcus aureus was the prevalent microorganism, this result was corroborated by other studies (8,25) . Regarding the mortality rate among patients with SSI, this research was 38.9%, diverging from other studies in which the frequency ranged between 2.6% and 32.1% (14,17,(22)(23)(24) . Therefore, this result indicated that the diagnosis of SSI was constituted in an aggravation of the clinical condition of the patient, which may have favored the occurrence of complications with death.…”
Section: Discussioncontrasting
confidence: 51%
“…In this study, the incidence of SSI was higher than that identified in the literature, ranging between 0.2% and 5.6% (8,10,16,(22)(23)(24)(25) . It is important to measure the rates of SSI, because they provide data that can lead to improvement of conditions observed and prevent this serious complication in patients undergoing cardiac surgery (5) .…”
Section: Discussioncontrasting
confidence: 45%
“…Previous studies investigating the association between early tracheostomy and deep sternal wound infection after median sternototomy showed divergent results: Whereas Ngaage et al 17 reported post-sternotomy PDT to be associated with an approximately 3-fold risk for deep sternal wound infections, others could not demonstrate any relationship between tracheostomy and mediastinitis. 18 In our cohort, none of the 14 subjects undergoing thoracic transplant with median sternotomy developed mediastinitis.…”
Section: Discussionmentioning
confidence: 77%
“…Tracheostomy prior to any identified SWI occurred in 411 patients (2.2%), and the median [IQR] time from post-surgical ICU admission to tracheostomy was 14 [10][11][12][13][14][15][16][17][18][19] Table 2. Tracheostomy was an independent predictor of SWI (adjusted OR 2.8; 95% CI 1.9 to 4.2).…”
Section: Resultsmentioning
confidence: 99%
“…There continues to be uncertainty as to the true nature of the relationship between tracheostomy and SWI, with recent publications both supporting and refuting tracheostomy as a cause of SWI post cardiac surgery. [5][6][7][8][9][10][11] Three large observational studies support tracheostomy as a risk factor for SWI. In a study of 6,057 patients undergoing isolated coronary artery bypass, Curtis et al 5 Two previous studies that failed to detect an association between tracheostomy and SWI were limited by small numbers of events, which precluded robust risk adjustment.…”
Section: Résumémentioning
confidence: 99%